2019
DOI: 10.3390/ma12142288
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis of the Fracture Evolution of Freeze-Thaw Damage to Asphalt Concrete

Abstract: AC (asphalt concrete)-13, as the main material used in pavement construction, has been applied widely in seasonal frozen areas. In order to understand the fracture mechanism in the freeze-thaw (F-T) damage process, the mesoscale structure of AC-13 is obtained by computed tomography (CT). The fractal dimension of cracks is used as a damage evaluation index. Most previous studies have only focused on the fractal dimensions of whole cracks, while ignoring the fractal tectonic process and the self-similarity degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The dependence in Figure 5b cannot be considered general, it is not final and requires further development and improvement. At the same time, it can be concluded that the development of damage is associated with a significant change in the interpore space and with the subsequent development of destruction due to the loss of connections between particles, which was proved by other authors earlier (El-Hakim & Tighe, 2014;Li et al, 2019;Shakiba, Al-Rub, Darabi, You, Masad, & Little, 2013;Si et al, 2015;Teltayev et al, 2019;Varveri et al, 2014;Xu, Guo & Tan, 2015, 2016. The development of these processes can be recorded by measuring, for example, the water saturation (residual porosity) of asphalt concrete during it being at work under appropriate influence (temperature, load, solar radiation, etc.).…”
Section: Experimental Studies Of Damageability Of Asphalt Concrete Pamentioning
confidence: 54%
See 1 more Smart Citation
“…The dependence in Figure 5b cannot be considered general, it is not final and requires further development and improvement. At the same time, it can be concluded that the development of damage is associated with a significant change in the interpore space and with the subsequent development of destruction due to the loss of connections between particles, which was proved by other authors earlier (El-Hakim & Tighe, 2014;Li et al, 2019;Shakiba, Al-Rub, Darabi, You, Masad, & Little, 2013;Si et al, 2015;Teltayev et al, 2019;Varveri et al, 2014;Xu, Guo & Tan, 2015, 2016. The development of these processes can be recorded by measuring, for example, the water saturation (residual porosity) of asphalt concrete during it being at work under appropriate influence (temperature, load, solar radiation, etc.).…”
Section: Experimental Studies Of Damageability Of Asphalt Concrete Pamentioning
confidence: 54%
“…To date, a number of studies have been carried out on the progressing of asphalt concrete damageability, for example, in the process of alternate freezing and thawing, which confirm the development of microcracks, their integration and enlargement with changes in the interpore space in the structure of asphalt concrete (Darabi, Abu Al-Rub, Masad, & Little, 2013;El-Hakim & Tighe, 2014;Kayhanian, Anderson, Harvey, Jones, & Muhunthan, 2012;Li, Wang, Yi, Ma, & Lin, 2019;Shakiba et al, 2013;Sung & Kim, 2012;Underwood, 2016;Varveri, Avgerinopoulos, Kasbergen, Scarpas, & Collop, 2014;Si et al, 2015;Teltayev, Rossi, Izmailova, & Amirbayev, 2019;Xu, Guo & Tan, 2015, 2016.…”
Section: Damageability Of Road Asphalt Concrete Pavementsmentioning
confidence: 96%
“…The new and connected voids of the mixture after freeze-thaw were found to be the direct factors influencing the amount of damage to the mixture. Li et al (2019a) obtained the internal microstructure of AC-13 using X-ray CT technology and simulated the critical crack stress in the process of freeze-thaw damage, considering that the critical crack stress weakened with an increase in freeze-thaw cycles. Lövqvist et al (2021) established a comprehensive multi-scale model including water permeability, temperature, and mechanical properties to simulate the influence of freeze-thaw cycles, freezing time, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are important because using SCMs as a partial replacement of Portland cement is necessary to mitigate the CO 2 emissions associated with using concrete and it improves the overall performance by doing so. In a study by Li et al [ 3 ], the authors investigated the intrinsic mechanism of fractures and damage induced by freeze–thaw in asphalt concrete and suggested the fracture model that can describe the fracture toughness during freeze–thaw cycles. The performance of cement-based materials can be evaluated by various tests as has been done by [ 2 , 3 ], while it can be investigated from a mechanistic viewpoint by employing various characterization techniques such as infrared spectroscopy, scanning electron microscopy [ 4 ], and backscattered electron image analysis [ 5 ].…”
mentioning
confidence: 99%
“…In a study by Li et al [ 3 ], the authors investigated the intrinsic mechanism of fractures and damage induced by freeze–thaw in asphalt concrete and suggested the fracture model that can describe the fracture toughness during freeze–thaw cycles. The performance of cement-based materials can be evaluated by various tests as has been done by [ 2 , 3 ], while it can be investigated from a mechanistic viewpoint by employing various characterization techniques such as infrared spectroscopy, scanning electron microscopy [ 4 ], and backscattered electron image analysis [ 5 ]. By employing these characterization techniques, Zeng et al [ 4 ] investigated the effect of temperature on the fluidity and early expansion characteristics of asphalt mortar, and Liu et al [ 5 ] observed the hardening behavior of beta-C 2 S in a carbonation condition.…”
mentioning
confidence: 99%